Performance evaluation of investment (mutual) funds - Vyšniauskas, Povilas; Rutkauskas, Aleksandras Vytautas (Business: Theory and Practice, 2014)
The efficiency of an investment fund is one of the main components in evaluating the performance of the fund. This study seeks for introducing and comparing risk and performance evaluation ratios. The paper is aimed at testing the worked out ratios and at distinguishing between the best ones for the purpose of evaluating the performance of Lithuanian mutual funds. Scientific studies show that a standard deviation, alpha, beta, Sharpe and Treynor ratios are mostly employed for identifying the performance of mutual funds that are also compared with their benchmark index to establish if these funds are outperformed and if is it worth paying management fees to investment banks for managing mutual funds. Historical data were selected for the period from 2012-01-02 to 2013-10-15 analysing the prices of monthly funds. The paper points out the areas of a practical application of the proposed model for investment fund valuation, which may not only provide valuable outcomes for practitioners but also may inspire further research on this article.